ISOLASI DAN KARAKTERISASI BAKTERI PROTEOLITIK ASAL TERASI IKAN SELUANG (Stolephorus sp.) - Oktavia, Yulia; Lestari, Shanti Dwita; Lestari, Susi; Baehaki, Ace; Kusuma, Dwiky Satya (Marinade, 2022)
Anchovy is one type of processed fishery product in Indonesia that is made through a fermentation process. The fish paste fermentation process utilizes the activity of hydrolytic bacteria present in the raw materials. These bacteria can produce hydrolytic enzymes capable of hydrolyzing complex molecules into simple ones. This study aims to isolate proteolytic bacteria and determine the character of the bacterial isolates obtained. The test results were analyzed descriptively. The test parameters carried out were determining the proteolytic index, colony and cell morphology tests, and biochemical tests.  4 bacterial isolates had proteolytic activity, namely PT1, PT2, PT3, and PT5. Based on biochemical tests, the PT2 isolate was suspected to be proteolytic lactic acid bacteria.